An improved anti-rollback control algorithm for gearless traction motor in elevator applications - Sawma, Jean; Seferian, Vahe; Khatounian, Flavia; Monmasson, Eric; Ghosn, Ragi (Mechatronics (Oxford), 2021)
Permanent magnet synchronous motors are widely used in elevator applications. This is due to their high efficiency and reliability, whereby motors are directly connected to the elevator ropes without the need of having a gearbox. This efficient system comes with some new challenges regarding the control of the motor. Since no gearbox is added to the system, the motor speed oscillations are directly transferred to the elevator cabin. This urges the need of having a smooth control algorithm to suppress the measurement noises generated by the absolute encoder especially at low speed. On the other hand, whenever the mechanical brakes are released, the speed controller needs to react quickly to prevent the cabin from rolling back. In order to overcome these challenges, this paper presents an improved speed control algorithm that reacts quickly in transient state to reduce the rollback of the cabin and slowly at steady state to ensure smooth ride. The proposed controller is based on the combination of a Model Predictive Controller (MPC) along with a torque observer. It also benefits from being computationally less demanding unlike other MPC techniques. The proposed controller is experimentally tested on an elevator and then compared to classic controllers. Finally, conclusions are drawn.